Taller Trabisílabas para desarrollar la lectura y escritura en estudiantes de una Institución Educativa, Trujillo - 2018 - Bocanegra Altamirano, Liliana Tomiko (2019)
The present investigation had like purpose, determining if the workshop Trabisilabas the influences the development of reading and writing of the students of the second grade of the Educational Institution significantly 80002 Antonio Torres Araujo, Trujillo – 2018._x000D_ This investigation was applied with quasi experimental design with a pre and after test, accomplished with 27 students sample in the group control and 27 students in the experimental group, of the second grase of the Educational Institution significantly 80002 Antonio Torres Araujo, Trujillo – 2018._x000D_ The results obtained when having applied the workshop evidenced than the workshop Trabisilabas have influence significantly in the development of the reading and writing in the students of the second grade of the Educational Institution significantly 80002 Antonio Torres Araujo, Trujillo – 2018.